Inflation and macroeconomic variable: evidence from developed countries [2008 – 2017] / Nurnajwa Hayati Andullah - Andullah, Nurnajwa Hayati (2022)
This project paper was carried out to find the relationship between inflation and macroeconomic variable (government spending, import, income and unemployment) from developed countries. This study was using panel data from 20 selected developed countries for the period 2008 until 2017 (10 years) only. The data was collected from The World Bank. Literature review was explained the significant and relationship between variables (inflation, government spending, import, income and unemployment). From the study, the result show that, three variables that significant to inflation which is government spending, import and income. Panel granger causality test show that there are two ways causality, one way causality and also no causality effect between all variables used.